2011
DOI: 10.1111/j.2042-7158.2011.01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Myrtenal inhibits acetylcholinesterase, a known Alzheimer target

Abstract: Our investigations provided evidence for the efficacy of monoterpenes as inhibitors of AChE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 26 publications
2
40
3
1
Order By: Relevance
“…The different activity of 3‐carene and 2‐carene is due to the position of the double bond and also oxygenated functional groups decrease the inhibition of AChE . Other researchers described a good AChE inhibitory activity for myrtenal (Figure a, Table ), an aldehyde, while Miyazawa and Yamafuji observed that myrtenol, an alcohol, does not have relevant activity . Savelev and collaborators studied the inhibition of BuChE by monoterpenoids.…”
Section: Terpenic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different activity of 3‐carene and 2‐carene is due to the position of the double bond and also oxygenated functional groups decrease the inhibition of AChE . Other researchers described a good AChE inhibitory activity for myrtenal (Figure a, Table ), an aldehyde, while Miyazawa and Yamafuji observed that myrtenol, an alcohol, does not have relevant activity . Savelev and collaborators studied the inhibition of BuChE by monoterpenoids.…”
Section: Terpenic Compoundsmentioning
confidence: 99%
“…[36] Cymserine is more potent than rivastigmine, due to the presence in cymserine of the basic structure of physostigmine, which is not present in rivastigmine [68] N.F. Limbatolide A 38.5 Electric eel [69] 22.3 Horse serum [69] Limbatolide B 47.2 Electric eel [69] 17.5 Horse serum [69] Limbatolide C 103.7 Electric eel [69] 14.2 Horse serum [69] Myrtenal 170 N.M. [70] N.F. Taraxerol 98.4 N.M. [71] N.F.…”
Section: -Carene 200mentioning
confidence: 99%
“…Two studies indicated its anti-tumor activity in vitro and in vivo [12], [13]. In the central nervous system, CAR was regarded as a potential drug for Alzheimer's disease due to its inhibitory effect on acetylcholinesterase (AChE) activity by using phenolic hydroxyl group of CAR to bind to AChE and leading to a loss of function of AChE [14], [15], [16]. In addition, CAR was found to have an antidepressant-like effect in mice by affecting the dopaminergic system [17].…”
Section: Introductionmentioning
confidence: 99%
“…praeteritum oils for anti-neurodegenerative activity via inhibition of acetylcholinesterase revealed that the oil A showed higher inhibitory effect with an IC50 of 0.74 mg/mL than the oil B (IC50 of 1.78 mg/mL). Anti-cholinesterase effects of 1,8-cineole, camphor and terpinen-4-ol which were the main constituents of the oil A have earlier been reported in a number of papers (34,(64)(65)(66).…”
Section: Free Radical Scavenging Activity (Dpph Assay)mentioning
confidence: 80%